Análisis inmunofenotípico de muestras normales de médula ósea: aplicaciones en el control de calidad en los laboratorios de citometría - Dian Carolina Roa-Higuera; Susana Fiorentino; Viviana Marcela Rodriguez-Pardo; Alba Myriam Campos-Arenas; Elvira Antonia Infante-Acosta; Claudia Cecilia Cardozo-Romero; Sandra Milena Quijano-Gómez (Universitas Scientiarum)
Immunophenotypic analysis of normal cell samples from bone marrow: applications in quality control of cytometry laboratories.Objective. To describe a standardized flow cytometry protocol for the relative and absolute quantification of hematopoietic cell subpopulationsfrom normal bone marrow, and to evaluate the expression of different lineage-specific cell markers with a reactivity associated to celldifferentiation to be used as part of the routine quality control in cytometry laboratories. Materials and methods. The immunophenotypicalanalysis of different cell subpopulations was done with samples from normal bone marrow using a panel of monoclonal and polyclonalantibodies useful in the characterization of acute leukemias with four different fluorescences, by means of a protocol that combines celllabeling of membrane and cytoplasm antigens. Expression analysis was done in terms of mean fluorescence intensity (MFI). Fluorescentbeads at a known concentration were added for calculating the absolute count of cells. Results. The antibody panel used allowed theidentification and quantification of different normal leukocyte subpopulations of lymphatic and myeloid origin, including CD34+ stem cells and more differentiated cell populations in the granulocytic, monocytic, and erythroid cell lines. We established reference values for cellpopulations and cell marker expression ranges as part of routine quality control of cytometry laboratories. Conclusion. Immunophenotypicpatterns identified as well as absolute and relative reference values for the different normal leukocyte populations from bone marrow can beused by cytometry laboratories as a basis for establishing reference parameters in phenotypic analyses of hematologic neoplasia.